(untitled) (Scottish Historical and Archaeological Internet Reports, 2010)
The prehistoric pottery assemblage represented a maximum of 29 vessels including Neolithic impressed wares, proto-Unstan bowls and Beakers. The lithic assemblage comprised 2788 artefacts almost all of flint. Four stray Mesolithic microliths were recovered along with a few early Neolithic pieces. Most of the artefacts were late Neolithic. A single sandstone boulder saddle quern of broad prehistoric date was recovered. Small samples of charcoal and charred plant remains included cereal grain, hazel, birch and oak charcoal.